Role of Artificial Intelligence in Teaching Pathology to Medical Students - Sarandeep Singh Puri; Neha Goel; Pradeep Garg (Wolters Kluwer Medknow Publications, 2024)
The applications of artificial intelligence (AI) have swiftly forayed into medical education. This study aimed to decipher the role of AI in teaching pathology to medical students, enlisting its potential benefits which include improved diagnostic accuracy, personalized learning experiences, and effective feedback mechanisms. It also brings into the light challenges and ethical considerations associated with incorporating AI in pathology education. This article provides a comprehensive idea about the current as well as prospects of AI in pathology in the long run.